Pharmacological correction of post-contrast acute kidney injury with a functional product based on fermented grape juice - Olesya V. Shcheblykina; Daria A. Kostina; Natalia G. Stoyanova; Igor A. Efremenko; Tatyana V. Avtina (Research Results in Pharmacology)
Introduction: Post-contrast acute kidney injury (PC-AKI) is a serious complication when takingiodine-containing radiopaque agents. The study is aimed at pharmacological correction of PK-AKIwith a functional product obtained from fermented red grape berry juice with a high content of stilbenoids (trans-resveratrol and its glycoside polydatin).